Recruiting and retaining general practitioners in rural practice: systematic review and meta‐analysis of rural pipeline effects. Issue 5 (21st July 2020) - Ogden, Jessica; Preston, Scott; Partanen, Riitta L; Ostini, Remo; Coxeter, Peter
Abstract: Objective: To synthesise quantitative data on the effects of rural background and experience in rural areas during medical training on the likelihood of general practitioners practising and remaining in rural areas. Study design: Systematic review and meta‐analysis of the effects of rural pipeline factors (rural background; rural clinical and education experience during undergraduate and postgraduate/vocational training) on likelihood of later general practice in rural areas. Data sources: MEDLINE (Ovid), EMBASE, Informit Health Collection, and ERIC electronic database records published to September 2018; bibliographies of retrieved articles; grey literature. Data synthesis: Of 6709 publications identified by our search, 27 observational studies were eligible for inclusion in our systematic review; when appropriate, data were pooled in random effects models for meta‐analysis. Study quality, assessed with the Newcastle–Ottawa scale, was very good or good for 24 studies, satisfactory for two, and unsatisfactory for one. Meta‐analysis indicated that GPs practising in rural communities was significantly associated with having a rural background (odds ratio [OR], 2.71; 95% CI, 2.12–3.46; ten studies) and with rural clinical experience during undergraduate (OR, 1.75; 95% CI, 1.48–2.08; five studies) and postgraduate training (OR, 4.57; 95% CI, 2.80–7.46; eight studies). Conclusion: GPs with rural backgrounds or rural experience during undergraduate or postgraduate medical training are more likely to practise in rural areas. The effects of multiple rural pipeline factors may be cumulative, and the duration of an experience influences the likelihood of a GP commencing and remaining in rural general practice. These findings could inform government‐led initiatives to support an adequate rural GP workforce. Protocol registration: PROSPERO, CRD42017074943 (updated 1 February 2018).